Sharp Filters To Extract Absence Seizures EEG Signals - Marchon, Niyan; Naik, Gourish (International Journal of Computer Sciences and Engineering, 2025)
Reliable and accurate analysis of the electroencephalogram (EEG) waveforms can be very important to the current medical research and clinical fraternity to analyze the EEG signals and accordingly treat the subjects for any neurological abnormalities such as seizures etc. This paper introduces the types of EEG and pin points the absence seizure (or petit mal seizures) among children. The paper analyses the use of a novel method of using a sharp finite impulse response (FIR) filter that can extract time domain EEG signals of patients who are inflicted with absence seizures. The sharp FIR filter comfortably extracts the noise free delta EEG frequency of 3.04Hz for a cutoff of 3Hz. The filter displays flat passband and stopband attenuation, and also possesses a linear phase response. A transition width of 1 Hz is achieved using our sharp filter